The route of joint of the transnational corporations and globalization - PISTOL, Luminiţa; UNGUREANU, Gabriela; UNGUREANU, Adrian; VÂRGĂ, Anca (Annals of Spiru Haret University. Economic Series, 2011)
Today’s discussions on globalization are more alive and controversial. As is acknowledged as a fact, globalization is studied not only as an economic category but as a process, system, phenomenon. Currently, on international level, a variety of companies operate. From all of these, the transnational corporation represent particular interest, being designated as an "entity-key of global economic activity, a creative net worth to devote a large proportion of global resources needed to sustain economic growth processes. The new trend in the TNC’s sites emphasize, efforts to promote corporate social responsibility that contributes to change the attitude of many corporations and individuals working for them. Company efforts are visible in contributions to community development and environmental impact. Corporations want to impose their own standards of development, which reflects some positive attitude towards regulations that support behavioral codes, which they argue. Globalization has opened the way for limited progress, offered alternatives to local development, has generated deep changes, n dimensional complex with sometimes unpre-dictable consequences on economic and socio-institutional development.